Synthesis of Amorphous MnO2/MWCNT Nanocomposites and Their Electrochemical Properties - Hu, Jie; Shi, Lina; Men, Jie; Wang, Lina (Asian Journal of Chemistry, 2014)
MnO2/MWCNT nanocomposites has been fabricated through a simple route in a water-reflux condenser system under different temperature. The as-prepared composites were characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction and Brunauer-Emmett-Teller surface area analysis. Capacitive properties of the synthesized composite electrodes were investigated via cyclic voltammetry, galvanostatic charge/discharge and electrochemical impedance spectrometry in a 0.5 M Na2SO4 electrolyte. Results show that this method can control the number and size of MnO2 particles loaded onto the surface of MWCNTs. Because excessive MnO2 enwrapping carbon nanotubes would affect the overall conductivity, the composite prepared by lower temperature has better characteristics of super capacitor. 60-MnO2/MWCNT composite (51 wt. % MnO2) displays the specific capacitance as high as 337 F/g at 1000 mA/g, which is higher than that of 100-MnO2/MWCNT (290 F/g) and exhibited an excellent cycling stability with no more than 6 % capacitance loss after 1000 cycles.